Tingkat Peramalan Penjualan Produk Bordir dan Sulaman Menggunakan Metode Trend Moment - Fellanie Mayesa Putri (Jurnal Informatika Ekonomi Bisnis, 2022)
Forecasting is data in the past that is used for the purposes of estimating future data. Selling is a managerial social process by which individuals and groups obtain what they need and want, create, offer, and exchange products of value with others. Yenie Embroidery and Embroidery Shop is a shop that is engaged in craftsmanship and sales of embroidery such as embroidery and embroidery, the results of craftsmen and embroidery located in Bukittingi. Currently Yenie Embroidery and Embroidery Stores are experiencing an increase both in terms of consumers and in terms of the type of merchandise. With the forecast can help to predict future sales and can minimize losses to a product. In this study, a forecast is carried out for the next month and to find out the success rate of the trend moment forecasting method for sales from Yenie Embroidery and Embroidery Shops through sales data. The method used in this research is the Trend Moment Method. The Trend Moment method is a method that uses certain statistical and mathematical methods to determine the function of a straight line as a substitute for a broken line formed by historical company data. The results of the study can forecast sales of embroidery and embroidery products properly and optimally. So that the store management can predict the inventory of goods for the future optimally. This action can improve service to the availability of goods very well